2021
DOI: 10.3390/foods10112758
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Specific Nanobodies and Their Application in the Rapid Detection of Nodularin-R in Water Samples

Abstract: Nanobodies have several advantages, including great stability, sensibility, and ease of production; therefore, they have become important tools in immunoassays for chemical contaminants. In this manuscript, nanobodies for the detection of the toxin Nodularin-r (NOD-R), a secondary metabolite of cyanobacteria that could cause a safety risk for drinks and food for its strong hepatotoxicity, were for the first time selected from an immunized Bactrian camel VHH phage display library. Then, a sensitive indirect com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The results of the two methods are basically the same. In addition, the nanobody, as an important tool in immunoassay for chemical contaminants, was developed and its efficiency was examined by detecting a secondary metabolite of cyanobacteria, namely nodularin (NOD-R) [11]. The ic-ELISA method based on the nanobody N56 was validated with spiked water sample and confirmed by UPLC-MS/MS, which indicated that the ic-ELISA established in this work is a reproducible detection assay for nodularin residues in water samples.…”
mentioning
confidence: 79%
“…The results of the two methods are basically the same. In addition, the nanobody, as an important tool in immunoassay for chemical contaminants, was developed and its efficiency was examined by detecting a secondary metabolite of cyanobacteria, namely nodularin (NOD-R) [11]. The ic-ELISA method based on the nanobody N56 was validated with spiked water sample and confirmed by UPLC-MS/MS, which indicated that the ic-ELISA established in this work is a reproducible detection assay for nodularin residues in water samples.…”
mentioning
confidence: 79%
“…NOD-R is a characteristic cyclic peptide composed of five amino acids. The first screening of Nbs against this cyanobacterial secondary metabolite toxin was conducted by Yang et al 104 However, these studies have also not yet been correlated with in vivo neutralization. Apart from the toxins mentioned above, there are also some common phytotoxins such as phytohemagglutinin, Capsule Lotus Root toxin, Solanine, and coniine.…”
Section: Nbs For Phytotoxin Neutralizationmentioning
confidence: 99%
“…Nanobodies used in water and soil allow the quick and accurate identification and detection of toxins and contaminants to the nanogram levels so, becoming a handy tool for these purposes [130][131][132] .…”
Section: Applications Of Camelid Nanobodies In Different Branches Of ...mentioning
confidence: 99%